2013
DOI: 10.1073/pnas.1211925110
|View full text |Cite
|
Sign up to set email alerts
|

Neurocomputational account of how the human brain decides when to have a break

Abstract: No pain, no gain: cost–benefit trade-off has been formalized in classical decision theory to account for how we choose whether to engage effort. However, how the brain decides when to have breaks in the course of effort production remains poorly understood. We propose that decisions to cease and resume work are triggered by a cost evidence accumulation signal reaching upper and lower bounds, respectively. We developed a task in which participants are free to exert a physical effort knowing that their payoff wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
121
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(129 citation statements)
references
References 41 publications
8
121
0
Order By: Relevance
“…Third, little is known about how the balance between reward and effort will develop over time in terms of learning or fatigue. We have found no evidence of significant trial sequence effects on our behavioral and neural outcomes at group level (results not reported) and experimental design will have to be optimized to investigate temporal trajectories (e.g., Meyniel et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…Third, little is known about how the balance between reward and effort will develop over time in terms of learning or fatigue. We have found no evidence of significant trial sequence effects on our behavioral and neural outcomes at group level (results not reported) and experimental design will have to be optimized to investigate temporal trajectories (e.g., Meyniel et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…We believe that such findings have applications in the domain of management, because the number and duration of work breaks could be adapted to avoid any dramatic LPFC dysfunction. If workers have control over their time schedule, they might spontaneously decide to take a break on the basis of some cost signal related to LPFC activity, as was shown with insular activity in the case of physical effort (39). Otherwise, LPFC dysfunction following overly intense cognitive work, with insufficient breaks, at longer time scales (weeks or months) might induce pathological conditions such as burnout syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence indicates that rapid bursts in VTA/SN neuronal firing rates correlate with expression of an appetitive reinforcement prediction error (RPE; D'Ardenne, McClure, Nystrom, & Cohen, 2008;Tobler, Fiorillo, & Schultz, 2005;Schultz, Dayan, & Montague, 1997). It has been suggested that tonic dopaminergic activity in VTA/SN also plays a key role in instrumental aspects of motivation by representing the average rate of reward (Skvortsova, Palminteri, & Pessiglione, 2014;Meyniel, Sergent, Rigoux, Daunizeau, & Pessiglione, 2013;Niv, Daw, Joel, & Dayan, 2007), which quantifies an opportunity cost of sloth and balances the price of alacrity.…”
Section: Introductionmentioning
confidence: 99%